2013
DOI: 10.1161/atvbaha.113.301848
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β–Activated Kinase 1 Regulates Angiogenesis via AMP-Activated Protein Kinase-α1 and Redox Balance in Endothelial Cells

Abstract: Objective— Transforming growth factor-β–activated kinase 1 (TAK1) is a mitogen-activated protein 3-kinase and an AMP-activated protein kinase (AMPK) kinase in some cell types. Although TAK1 −/− mice display defects in developmental vasculogenesis, the role of TAK1 in endothelial cells has not been investigated in detail. Approach and Results— TAK1 downregulation (small interfering RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…The ability of endothelial cells to form capillarylike structures was assessed as previously described (Zippel et al, 2013). Briefly, primary cultures of endothelial cells (1 Â 10 4 cells) were seeded onto angiogenesis microscope slides (m-Ibidi, Martinsried, Germany) coated with Matrigel.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of endothelial cells to form capillarylike structures was assessed as previously described (Zippel et al, 2013). Briefly, primary cultures of endothelial cells (1 Â 10 4 cells) were seeded onto angiogenesis microscope slides (m-Ibidi, Martinsried, Germany) coated with Matrigel.…”
Section: Methodsmentioning
confidence: 99%
“…In several recent studies, a possible role of TAK1 as upstream mediator of AMPK activation was verified by applying genetic knockdown strategies [34,35,36,37,38,39]. Although not verifying the role of TAK1 as a direct AMPK kinase, this approach puts TAK1 as an upstream AMPK activating signal into various cellular contexts.…”
Section: What Is the Cellular Condition Where Tak1 Acts As An Upstmentioning
confidence: 99%
“…Moreover, Ciccarelli et al 7 demonstrated that endothelial G-protein-coupled receptor kinase 2 removal induces endothelial dysfunction by increasing endothelial ROS production. Furthermore, Zippel et al 8 demonstrated that transforming growth factor-β-activated kinase 1 regulates redox balance in ECs by AMP-activated protein kinase α1, which acts as a metabolic master switch regulating several intracellular systems. In addition, Iso et al 9 clearly demonstrated that capillary endothelial fatty acid-binding protein 4/5 is required for fatty acid transport into fatty acid-consuming tissues, including the heart, which controls the metabolism of energy substrates in fatty acid-consuming organs.…”
Section: Ecs For Vascular Functionmentioning
confidence: 99%